Finding the "Me" for Building the "We": Building Community Based Support Groups for Survivors of Violence Against Women - Rivera, Roselle Leah K. (Review of Women's Studies; Vol 11 No 1-2 (2001): Review of Women's Studies Volume XI, Numbers 1-2 (January-December 2001))
The paper discusses what feminist action research is all about and how this was used to enable VAW survivors to see themselves not as mere victims but as persons with the power to transform themselves into agents of self redemption and active members of a VAW support group and/or anti-VAW advocacy formation.